2018
DOI: 10.2147/opth.s185274
|View full text |Cite
|
Sign up to set email alerts
|

Safety of high-dose intravitreal triamcinolone acetonide as low-cost alternative to anti-vascular endothelial growth factor agents in lower-middle-income countries

Abstract: PurposeThe purpose of this study was to evaluate the safety of high-dose intravitreal triamcinolone acetonide (IVTA) as affordable low-cost alternative to anti-vascular endothelial growth factor (anti-vascular endothelial growth factor [anti-VEGF] agents) in lower-middle-income countries.Patients and methodsThis was a retrospective interventional non-comparative case series. The study recruited patients who received 20 mg IVTA for treating various retinal and optic nerve diseases over the past 5 years. Main ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…However, different corticosteroids were not directly compared in a single study to explore their relative efficacy. Meanwhile, in view of the high cost of DEX and FA implants, especially for lower-middle-income countries, evaluating the value of intravitreal TA as a low-cost alternative for DME patients is still worthwhile [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, different corticosteroids were not directly compared in a single study to explore their relative efficacy. Meanwhile, in view of the high cost of DEX and FA implants, especially for lower-middle-income countries, evaluating the value of intravitreal TA as a low-cost alternative for DME patients is still worthwhile [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…10,11 According to literature, median number of injections required for DME in a single patient ranged from 9-11 in first year of treatment and mount to 17 injections over 5 years. 4,12 Based on a simulated model of one year follow up of RESTORE trial, incremental cost for ranibizumab is ₤4,191 for 0.17 Quality Adjusted Life Year (QALY) and may reach ₤ 24,028 for estimated 15 year time. 4 The efficacy of IVTA in treating DME is also well proven over the last many decades.…”
Section: Discussionmentioning
confidence: 99%
“…4,12 Based on a simulated model of one year follow up of RESTORE trial, incremental cost for ranibizumab is ₤4,191 for 0.17 Quality Adjusted Life Year (QALY) and may reach ₤ 24,028 for estimated 15 year time. 4 The efficacy of IVTA in treating DME is also well proven over the last many decades. But repeated studies have shown very high occurrence of cataract formation and increased IOP over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although injection of Ozurdex has become the main treatment for macular edema in recent years[1], TA injection is an effective and inexpensive treatment and is still used in developing countries or regions. Recent research has indicated that intravitreal injection of TA is an efficient approach in the treatment of a variety of proliferative, edematous, neovascular and inflammatory ocular disorders[2-4]. Despite the efficacy of intravitreal TA injection, attention should be paid to its associated complications.…”
Section: Introductionmentioning
confidence: 99%